40 Age-related modification of heparan sulphate proteoglycans on human endothelial progenitor cells. Issue 20 (23rd September 2011) - Williamson, K; Stringer, S E; Sipos, P; Crocker, I; Alexander, M Y
Abstract : Accumulating evidence indicates that vascular repair by endothelial progenitor cells (EPCs) is impaired with age. However, the molecular mechanisms underlying this functional impairment are not understood. Cell-surface heparan sulphate (HS) proteoglycans, by virtue of specific sulphated domains within the glycosaminoglycan chain, are able to bind a variety of ligands essential for EPC mobilisation, homing and differentiation. We hypothesise that structural changes of HS on EPCs contribute to vascular dysfunction in age and disease. Using umbilical cord blood, and adult peripheral blood from young and old subjects, we routinely isolate a rare population of EPCs, termed outgrowth endothelial cells (OECs). These cells are highly proliferative, express a panel of endothelial but not haematopoietic markers, can ingest Ac-LDL and form tubes in Matrigel. Structural analysis of HS by high performance liquid chromatography (HPLC) demonstrates a reduction of 6-O-sulphation of HS on the surface of OECs with vascular age. There is 21.9% 6-O-sulphation of HS chains on cord blood OECs compared to 14.6% and 10.1% on adult peripheral blood OECs from young (20–30 years) and older (>55 years) subjects respectively. Moreover, these HS structural changes correlate with a decrease in the proliferative and migratory capacities of these cells. The effects of these changes on the response of EPCs to signalling molecules implicated in EPC mobilisation and homing (VEGF and SDF-1) are currently being investigated. Whether the impairment in function can be rescued by the addition of soluble heparin is also being assessed. This work could have clinical relevance for therapeutic angiogenesis in patients with limb ischemia or vascular damage.